If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 6)(X + -8)(2x + -7) = 0 Reorder the terms: (6 + X)(X + -8)(2x + -7) = 0 Reorder the terms: (6 + X)(-8 + X)(2x + -7) = 0 Reorder the terms: (6 + X)(-8 + X)(-7 + 2x) = 0 Multiply (6 + X) * (-8 + X) (6(-8 + X) + X(-8 + X))(-7 + 2x) = 0 ((-8 * 6 + X * 6) + X(-8 + X))(-7 + 2x) = 0 ((-48 + 6X) + X(-8 + X))(-7 + 2x) = 0 (-48 + 6X + (-8 * X + X * X))(-7 + 2x) = 0 (-48 + 6X + (-8X + X2))(-7 + 2x) = 0 Combine like terms: 6X + -8X = -2X (-48 + -2X + X2)(-7 + 2x) = 0 Multiply (-48 + -2X + X2) * (-7 + 2x) (-48(-7 + 2x) + -2X * (-7 + 2x) + X2(-7 + 2x)) = 0 ((-7 * -48 + 2x * -48) + -2X * (-7 + 2x) + X2(-7 + 2x)) = 0 ((336 + -96x) + -2X * (-7 + 2x) + X2(-7 + 2x)) = 0 (336 + -96x + (-7 * -2X + 2x * -2X) + X2(-7 + 2x)) = 0 (336 + -96x + (14X + -4xX) + X2(-7 + 2x)) = 0 (336 + -96x + 14X + -4xX + (-7 * X2 + 2x * X2)) = 0 (336 + -96x + 14X + -4xX + (-7X2 + 2xX2)) = 0 Reorder the terms: (336 + 14X + -7X2 + -96x + -4xX + 2xX2) = 0 (336 + 14X + -7X2 + -96x + -4xX + 2xX2) = 0 Solving 336 + 14X + -7X2 + -96x + -4xX + 2xX2 = 0 Solving for variable 'X'. The solution to this equation could not be determined.
| -8(t+9)=6 | | 3x-1+4x+3=180 | | 5b^2+31b+30=0 | | y^2-4x^2=16 | | 6=7s-4 | | 2+2p=2-2p | | 1.82=Log(x) | | 2(-4)-3=x | | 5x+4=6x-42+8 | | 7+m=6 | | 2p+4p-7x+3=4p+5-3x | | -5x-6=-1 | | V^2-2v-5=-3v-3 | | 12x-8=15x-14 | | -5(x-3)=5(x-3) | | 5m+3n-2m-8n= | | (x+2)(7x+8)=0 | | 9-4+5h+3x= | | 9x/2=3x | | 9-4+53+32= | | 25c^2-121g^2=0 | | Y=3/4x-9;(-8,-18) | | 4y+10=-26 | | (14x+5)+(10x+15)=80 | | 6x+10=9x-11 | | 8n-3=15+2n | | 6y-9=45 | | 3/1*(8X/7-9/7) | | 3/1*(8X-9/7) | | 12x^3+6x^2-5x-3=0 | | 2m^2+9m+17=8 | | 3x+6-2=10 |